2017
DOI: 10.1093/annonc/mdx193
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of everolimus plus octreotide LAR in patients with advanced neuroendocrine tumor and carcinoid syndrome: final overall survival from the randomized, placebo-controlled phase 3 RADIANT-2 study

Abstract: NCT00412061, www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 9 publications
1
61
1
1
Order By: Relevance
“…Nevertheless, dedicated analyses from the most recent prospective placebo-controlled trials , Pavel et al 2017b) demonstrated no CgA role for predicting the impact of a medical treatment on survival. However, it is important to remark that CgA, per definition, can be used as a marker only in NENs showing abnormal serum level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, dedicated analyses from the most recent prospective placebo-controlled trials , Pavel et al 2017b) demonstrated no CgA role for predicting the impact of a medical treatment on survival. However, it is important to remark that CgA, per definition, can be used as a marker only in NENs showing abnormal serum level.…”
Section: Resultsmentioning
confidence: 99%
“…This thesis was subsequently confirmed by RADIANT-2 and -3, which were randomized, placebocontrolled trials of everolimus in advanced NENs with carcinoid syndrome under SSA treatment and advanced pancreatic NENs, respectively (Pavel et al 2011, Yao et al 2011b. Indeed, recent post hoc analyses of both studies specifically assessed whether baseline CgA levels were only prognostic or had actual capability of predicting treatment effect on OS , Pavel et al 2017b. This was done by adjusting OS of the 2 study arms for pre-treatment CgA levels, which were imbalanced.…”
Section: Baseline Cga As Predictive Marker Of Treatment Efficacymentioning
confidence: 88%
See 1 more Smart Citation
“…The results of the RADIANT trial series[20–23] and sub-analyses[59–71] are summarized in Table 1. The efficacy of everolimus in NETs was initially investigated in the RADIANT-1 trial, an open-label, phase II pilot dose-finding study involving patients with metastatic, low- to intermediate-grade NETs of pancreas, small bowel, and lung origin[20].…”
Section: Efficacy Of Everolimusmentioning
confidence: 99%
“…This result may have been affected by the imbalance of patient characteristics between the everolimus and the control arms (i.e., WHO performance status, lung origin). Several sub-group analyses were performed from the results of the RADIANT-2 trial (Table 1)[5964]. Although the numbers were small, everolimus plus octreotide demonstrated superior anti-tumor activity in patients with lung[60] and colorectal NETs[61].…”
Section: Efficacy Of Everolimusmentioning
confidence: 99%